Genome Diversity of Epstein-Barr Virus from Multiple Tumor Types and Normal Infection - Palser,AL; Grayson,NE; White,RE; Corton,C; Correia,S; Abdullah,MMB; Watson,SJ; Cotten,M; Arrand,JR; Murray,PG; Allday,MJ; Rickinson,AB; et al. (Journal of Virology, 2015)
Epstein-Barr virus (EBV) infects most of the world’s population and is causally associated with several human cancers, but littleis known about how EBV genetic variation might influence infection or EBV-associated disease. There are currently no publishedwild-type EBV genome sequences from a healthy individual and very few genomes from EBV-associated diseases. We havesequenced 71 geographically distinct EBV strains from cell lines, multiple types of primary tumor, and blood samples and thefirst EBV genome from the saliva of a healthy carrier. We show that the established genome map of EBV accurately represents allstrains sequenced, but novel deletions are present in a few isolates. We have increased the number of type 2 EBV genomes sequencedfrom one to 12 and establish that the type 1/type 2 classification is a major feature of EBV genome variation, definedalmost exclusively by variation of EBNA2 and EBNA3 genes, but geographic variation is also present. Single nucleotide polymorphism(SNP) density varies substantially across all known open reading frames and is highest in latency-associated genes. SomeT-cell epitope sequences in EBNA3 genes show extensive variation across strains, and we identify codons under positive selection,both important considerations for the development of vaccines and T-cell therapy. We also provide new evidence for recombinationbetween strains, which provides a further mechanism for the generation of diversity. Our results provide the firstglobal view of EBV sequence variation and demonstrate an effective method for sequencing large numbers of genomes to furtherunderstand the genetics of EBV infection.